Entrepreneurial orientation and corporate social responsibility: a focus on South African firm performance African firm performance - Saini, Mwila (My University, 2019)
Entrepreneurial Orientation incorporates firm-level processes, practices, and decision-making styles reflective of entrepreneurial behavioural involving the combination of innovativeness, risk taking, and proactiveness. CSR is defined, as a holistic set of activities and initiatives that primarily meet the economic, social and environmental triple bottom line needs of relevant stakeholders. The study looked at firms in South Africa participating in CSR projects and initiatives to exploring the relationship between a firm’s level of entrepreneurial orientation (EO), its CSR Activity, management performance and firm business performance. The study applied a quantitative method to analyze the relationship between the Entrepreneurial Orientation and the independent variables of management performance, business performance and CSR among 170 respondents. The empirical findings of the study revealed that EO had a positive effect on CSR activity and business performance indicators. The study finds that entrepreneurs, managers and CSR practitioners can configure CSR as a business tool that can contribute to the competitiveness of an enterprise as well as positively contribute to the developmental agenda of the environments enterprises operate in.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation, April 2019
Keywords: Entrepreneurship--South Africa; Business enterprises--South Africa; Entrepreneurship